Human intraparietal sulcus (IPS) and competition between exogenous and endogenous saccade plans. - Anderson, E; Husain, M; Sumner, P (2008)
How are stimulus-driven reflexes generated, and what controls their competition with voluntary action? The saccadic reflex to look towards an abrupt visual onset (prosaccade) has been associated with the retinotectal and magnocellular pathways, which rapidly convey signals to the superior colliculus and cortical eye fields. Such stimulus-driven reflexes need to be suppressed when making an eye movement in the opposite direction (antisaccade), resulting in a cost in saccade latency. We compared the latencies of pro- and anti-saccades elicited by conventional luminance stimuli with those evoked by stimuli visible only to short-wave-sensitive cones (S cones) embedded in dynamic luminance noise. Critically, the retinotectal and magnocellular pathways are functionally blind to such stimuli. Compared to luminance stimuli, antisaccade latency costs were significantly reduced for 'S-cone' stimuli. This behavioural interaction is consistent with reduced competition between reflexive and endogenous saccade plans when S-cone stimuli are employed, while other processes involved in making an antisaccade, such as changing preparatory set or generating an endogenous saccade, are predicted to be equivalent for each kind of stimulus. Using fMRI, we found that activity in the right intraparietal sulcus (IPS) mirrored the behavioural interaction in saccade latencies. Thus, the right IPS appears to index the degree of competition between exogenous and endogenous saccade plans, showing the activity pattern predicted for an area involved in suppressing the saccade reflex. Furthermore, signals recorded from the superior colliculus showed the reverse pattern of responses, consistent with a direct inhibitory influence of IPS on SC.